Sanksi atas Pembunuhan Syibhu al-'Amd dalam Perspektif Fikih Jinayah - Muh. Taufiqurrahman; Irwan Fitri Aco; Muhammad Saddam Nurdin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the sanctions for the murder of syibhu al-'amd in the perspective of jinayah jurisprudence and to find out the implications for the application of these sanctions. The type of research used is qualitative descriptive research (non-statistical), using library research methods and normative approach methods and philosophical methods. As a result of this study, it was found that the sanctions for the killing of syibhu al-'amd were diyat and kaffārat. So it is different from intentional murder whose punishment is qiṣāṣ, and different from accidental murder in its type of diyat, namely diyat mugallaẓah. The murder of syibhu al-'amd was deliberate in carrying out its actions, but not deliberately in killing the victim so that it deserves relief in the form of diyat payments borne by 'āqilah perpetrators and payments are not cash or given a period of three years. Another sanction for the killing of syibhu al-'amd is ta'zīr, which is enforced if the sanction is terminated for some reason. In addition, an additional sanction for the perpetrator of the murder of syibhu al-'amd is the prohibition of inheritance and wills as a consequence of the murder he committed. The implications or impacts that occur from the application of diyat sanctions on the perpetrators of the murder of syibhu al-'amd are to provide a peaceful life for the community, deter perpetrators of crime and murder, prevent from various tyrannies, and reduce the occurrence of murder. The application of diyat sanctions can also have bad implications because the perpetrator of the murder of syibhu al-'amd is not punished with qiṣāṣ sanctions, the perpetrator may think hopefully in killing, because the perpetrator thinks there is still a family that he can rely on in bearing the payment of diyat